DENSE GLASS FOAM PRODUCED IN MICROWAVE FIELD - LUCIAN PAUNESCU (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2018)
Experimental results obtained in the process of manufacturing dense glass foam using the microwave energy are presented in the work. The glass foam is produced from bottle glass waste, calcium carbonate as foaming agent and borax as fluxing agent. The high compressive strength (2.5 - 6.2 MPa) is the main mechanical feature of this product, which together with other physical and morphological features (apparent density 0.60 – 0.90 g/cm3, porosity 59.1 – 72.7%, thermal conductivity 0.081 – 0.105 W m K, water absorption 0.5 – 1.0%, pore size 0.5 – 3 mm), are appropriate for using as a substitute for similar building materials existing on the market.